Program Mini Segmen “Kampung Jatim” Sebagai Pengembangan Program Berita Televisi "Pojok Kampung" JTV (Studi Kasus Respons Pemirsa JTV Di Kelurahan Bulak Banteng Surabaya) - Wachid Abdillah; Dhimam Abror Djuraid; Nur Annafi (Wahana, 2023)
Entering the era of terrestrial digital television, many new television stations have emerged, JTV, the name of the television station from (PT. Jawa Pos Media Televisi) is the largest local television in East Java, there are many controversies about the pros and cons, including the mainstay news program Pojok Kampung which is one of the top programs on JTV , this news program is unique in its disclosure, namely using boso Suroboyoan. This research is descriptive research with a qualitative approach. The data types used are primary and secondary. Primary data sources come from interviews, FGDs, observations, surveys and documentation. Secondary sources of information are obtained from scientific journals, theses, theses and various literature sources related to research. The results of this research, the existence of the Kampung Jatim mini segment program is the result of the ideas and ideas of the Pojok Kampung JTV editorial team to be able to bring back news programs using typical native languages ​​from several regions in East Java such as Madurese, Kulonan Javanese and Osing. in one mini segment namely Kampung Jatim with the aim of strengthening the village corner program itself and also as a forum for preserving the cultures and languages ​​in East Java. The response to JTV viewing in the Bulakbull sub-district is proven by the results of the FGD which is in line with showing that it has a positive trend or successful in the development and innovation process of the Village Corner program